2013
DOI: 10.1080/02757540.2013.841892
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Arbuscular mycorrhizal fungi isolated from white clovers (Trifolium repensL) on soil bacteria and fungi

Abstract: White clover potted experiments were performed to investigate the effects of seven indigenous arbuscular mycorrhizal fungi (AMF) communities isolated from different test plots subjected to long-term fertilisation on soil enzyme activities, number of soil bacteria and fungi. The results showed that the inoculation of arbuscular mycorrhizal fungi communities increased the mycorrhizal infection rate of the plants and promoted the growth of plants. The Mnp treatment was most effective. The shoot biomass, root biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The study demonstrated that AMF inoculation increased nodulation and N fixation, which in turn improved N nutrition. Similarly, a study done by Huang et al (2014), on white clover (Trifolium repens) found a significant correlation between percentage AMF colonization and number of nodules. Nonetheless, contrary findings were obtained in alfalfa (Catford et al 2003), whereby colonization of roots with AMF systematically inhibited further mycorrhization as well as nodule formation.…”
Section: Amf Colonization and Cowpea Growthmentioning
confidence: 65%
“…The study demonstrated that AMF inoculation increased nodulation and N fixation, which in turn improved N nutrition. Similarly, a study done by Huang et al (2014), on white clover (Trifolium repens) found a significant correlation between percentage AMF colonization and number of nodules. Nonetheless, contrary findings were obtained in alfalfa (Catford et al 2003), whereby colonization of roots with AMF systematically inhibited further mycorrhization as well as nodule formation.…”
Section: Amf Colonization and Cowpea Growthmentioning
confidence: 65%
“…Spearman correlation analysis revealed that three genera, Claroideoglomus , Dominikia , and Funneliformis , were significantly negatively correlated with urease, showing a negative effect of urease and total nitrogen. AMF inoculation is known to increase the soil urease, convertase, and cellulase activities ( 23 ). Ammonia, an enzymatic product of urease, is not irreplaceable.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in quantity and diversity at the genus level of the AMF communities leads to different amounts of root exudates. These differences lead to different soil invertase activity and cellulase activity ( 23 ). Besides, soil dehydrogenases are closely related to soil respiratory metabolism, citric acid cycle, and nitrogen metabolism and can be used to represent the metabolic activities of soil microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…showed that inoculation with mycorrhizal fungi significantly increased the number of fungi in soil in which white clover was growing but had little effect on the number of bacteria in the soil, while Li et al . found that AMF increased the numbers of bacteria and actinomycetes and reduced the number of fungi [ 41 , 42 ]. Here, AMF improved the rhizosphere microenvironment, nutrient status and organic matter content, together with the acid phosphatase activity, which may have contributed to the increase in the number of microorganisms and in the metabolic activity of the rhizosphere.…”
Section: Discussionmentioning
confidence: 99%